Effects of gluten exclusion in the diet of patients with Hashimoto's thyroiditis (Research, Society and Development, 2025)
The objective of this study was to analyze the effects of adopting a gluten-free diet in patients with Hashimoto’s thyroiditis. Hashimoto’s thyroiditis (HT) is the leading cause of hypothyroidism in countries with adequate iodine intake and is characterized by the presence of autoantibodies (anti-TPO and anti-Tg) and lymphocytic infiltration of the thyroid. Recent studies have investigated gluten exclusion as a complementary nutritional strategy in disease management. This literature review analyzed publications from 2015 to 2025 on the relationship between a gluten-free diet (GFD) and thyroid autoimmunity. Results are mixed: some patients showed reductions in autoantibodies, slight improvements in thyroid hormones, and decreases in symptoms such as fatigue and gastrointestinal discomfort; however, most evidence remains inconclusive. Diets rich in antioxidants, omega-3s, and essential minerals show more consistent effects on thyroid health than simply removing gluten. It is concluded that a GFD may be useful as an adjunct approach in specific cases—especially in the presence of gastrointestinal symptoms or a diagnosis of celiac disease—but should not be recommended indiscriminately. The decision to exclude gluten should be individualized and guided by a nutrition professional. Larger, long-duration randomized clinical trials are needed to strengthen current evidence and inform safer practice.